Low transmission risk of Pseudomonas aeruginosa in a bronchiectasis clinic based on the knowledge of bacterial population biology. Issue 3 (28th March 2019) - Cramer, Nina; Sedlacek, Ludwig; Tümmler, Burkhard; Welte, Tobias
The nosocomial acquisition of opportunistic pathogens, particularly Pseudomonas aeruginosa, has been repeatedly documented in individuals with cystic fibrosis (CF) [1]. Cross-infection is also a concern in bronchiectasis not due to CF [2]. This issue was not addressed by the European Respiratory Society 2017 guidelines for the management of adult bronchiectasis [3] but the European Bronchiectasis Network (EMBARC), the EMBARC Patient Advisory Group and the European Reference Network (ERN-Lung) Bronchiectasis Network released a position statement in the European Respiratory Journal in 2018 [4]. Based on the available evidence, the risk of cross-infection with P. aeruginosa was judged to be small. This study suggests that the risk of cross-infection with P. aeruginosa in bronchiectasis is small http://ow.ly/itUa30nrgET